2019
DOI: 10.1111/spc3.12433
|View full text |Cite
|
Sign up to set email alerts
|

Catching aggression from one's peers: A longitudinal and multilevel analysis

Abstract: Exposure to peer aggression is a major risk factor for the development of aggressive behavior in childhood and adolescence. Furthermore, peer aggression has the propensity to spread and affect individuals who were not exposed to the original source of aggression. The aim of this paper is to demonstrate that peer aggression is in many regards similar to a contagious disease. By presenting a program of research based on longitudinal and multilevel studies, we provide evidence for the contagious quality of aggres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 39 publications
(60 reference statements)
4
14
0
1
Order By: Relevance
“…However, in line with the spreading of aggression as a contagious disease, our findings showed that aggressive classroom environments have a greater impact on initially nonaggressive children than on those with higher levels at the start of the analysis ( Jung et al, 2019). In their sample of children of elementary school age, Rohlf et al (2016) found that children who showed low initial levels of relational aggression scored significantly higher on measures of relational aggression 10 months later if they were in classrooms with a high level of relational aggression.…”
Section: Interaction Of Personal and Environmental Risk Factors: The supporting
confidence: 78%
See 1 more Smart Citation
“…However, in line with the spreading of aggression as a contagious disease, our findings showed that aggressive classroom environments have a greater impact on initially nonaggressive children than on those with higher levels at the start of the analysis ( Jung et al, 2019). In their sample of children of elementary school age, Rohlf et al (2016) found that children who showed low initial levels of relational aggression scored significantly higher on measures of relational aggression 10 months later if they were in classrooms with a high level of relational aggression.…”
Section: Interaction Of Personal and Environmental Risk Factors: The supporting
confidence: 78%
“…In a series of longitudinal studies, we investigated the contagious spread of aggressive behavior in classrooms attended by elementary and secondary school students (see Jung, Busching, & Krahé, 2019, for a review). In these studies, we showed that individual aggressive and antisocial behavior increases over time in classrooms with a higher collective level of aggressive behavior, compared with classrooms in which the overall level of aggressive and antisocial behavior is lower (Busching & Krahé, 2015, 2018; Rohlf, Krahé, & Busching, 2016).…”
Section: Interaction Of Personal and Environmental Risk Factors: The mentioning
confidence: 99%
“…A broad research literature has demonstrated the influence of peers on adolescents' behavior in a variety domains. The focus of this research has been on problem behaviors, such as smoking and drinking (Ragan 2020;Vitória et al 2020), problematic social media use (Marino et al 2020), and aggressive and antisocial behavior (Jung et al 2019).…”
Section: The Influence Of Peers On the Development Of Prosocial Behaviormentioning
confidence: 99%
“…It is well documented that adolescent friends are similar in aggressive behavior. [17][18][19] Children and adolescents who have aggressive friends become more antisocial over time themselves, indicating a socialization effect. Adolescents also tend to choose friends with similar levels of aggression as themselves, although support for this selection effect is more limited.…”
Section: Violent Games and The Social Networkmentioning
confidence: 99%
“…First, similarity in friends' aggressive behavior may be explained by both selection and socialization effects. 17,19 That is, adolescents initiated friendships with peers who had similar levels of aggression, and friends became more similar in aggression over time. Second, similarity in friends' VVE was better explained by selection than socialization.…”
Section: Social Network Effects Of Violent Video Games 27mentioning
confidence: 99%